Clinical possibilities of HER2-positive breast cancer diagnosis using alternative scaffold proteins - O. D. Bragina; V. I. Chernov; S. M. Deyev; V. M. Tolmachev (Бюллетень сибирской медицины)
HER2-positive breast cancer occurs in 15–20% of breast cancer patients and is associated primarily with a poor prognosis of the disease and the need for highly specific targeted therapy. Despite the clinical importance of determining HER2/neu, traditional diagnostic methods have their disadvantages and require the study of new additional research techniques.The information presented in this review makes it possible to consider current trends in the radionuclide diagnosis of HER2-positive breast cancer using the latest class of alternative scaffold proteins and to consider various aspects of their use in clinical practice.